Guidance on safety evaluation of sources of nutrients and bioavailability of nutrient from the sources. (26th June 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipicč, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: Whenever new substances are proposed for use as sources of nutrients in food supplements, foods for the general population or foods for specific groups, EFSA is requested by the European Commission to perform an assessment of their safety and of the bioavailability of the nutrient from the proposed source. This guidance describes the scientific data required to allow an evaluation of the safety of the source within the established framework for risk assessment of food additives and novel food ingredients and the bioavailability of the nutrient from this source. This document is arranged in five main sections: one on technical data aimed at characterising the proposed source and at identifying potential hazards resulting from its manufacture and stability in food; one on existing authorisations and evaluation, providing an overview of previous assessments on the proposed source and their conclusions; one on proposed uses and exposure assessment section, allowing an estimate of the dietary exposure to the source and the nutrient based on the proposed uses and use levels; one on toxicological data, describing approaches which can be used to identify (in conjunction with data on manufacture and composition) and to characterise hazards of the source and any relevant breakdown products; the final section on bioavailability focuses on determining the extent to which the nutrient from the proposed source is available for use by the body in comparison with one or more forms of the same nutrient that are already permitted for use on the positive lists. This guidance document should replace the previous guidance issued by the Scientific Committee for Food and published in 2001. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1439/full